Pelatihan Personel Pemandu Parkir Pesawat Udara (Marshalling) Bagi Personel Bandar Udara - Kardi, Kardi; Agustono, Agustono; Sundoro, Sundoro; Adriansyah, Feri; Pratiwi, Ayu Kumala; Kusumah, M. Chandra (Jurnal Pengabdian Kepada Masyarakat, 2024)
Aircraft parking guide personnel training (marshalling) is training that is carried out to increase competence and knowledge for Aviation Human Resources related to aircraft parking guide procedures and services. The competency standards for aircraft parking guide personnel as stipulated in the Minister of Transportation Regulation Number PM 37 of 2021 concerning airport personnel states that each aircraft parking guide personnel is expected to be able to handle fixed wings aircraft parking guide activities, able to guide fixed wings aircraft with hand signals. This training is given to aviation personnel at stakeholders / aviation companies who do not yet have a marshalling certificate at agencies around the Indonesian Aviation Polytechnic Curug (PPI Curug). This training needs to be held with the aim of increasing the competence of professional and reliable human resources in the field of Aviation, in line with applicable regulations related to airport personnel certification. In addition to gaining knowledge and skills, trainees will get a marshalling competency certificate as the final result of this training activity.